2015
DOI: 10.1016/j.addbeh.2014.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Social judgments of behavioral versus substance-related addictions: A population-based study

Abstract: The general public appreciates the complex bio-psycho-social etiology underlying addictions, but perceives substance-related and behavioral addictions differently. These attitudes, in turn, may shape a variety of important outcomes, including the extent to which people believed to manifest behavioral addictions feel stigmatized, seek treatment, or initiate behavior changes on their own.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 42 publications
(47 reference statements)
3
28
0
1
Order By: Relevance
“…The fi gures were slightly lower when respondents were asked about the past 30 days (15.6%). Although this was a young at-risk sample that reported significantly higher than normal levels of substance-based addictions, the difference with the general adult population in relation to this particular addiction within a 12-month period did not differ signifi cantly from large adult samples from Canada, where work and eating were the most prevalent behavioral addictions (Konkolÿ Thege et al, 2015).…”
Section: Prevalence Of Workaholismmentioning
confidence: 59%
“…The fi gures were slightly lower when respondents were asked about the past 30 days (15.6%). Although this was a young at-risk sample that reported significantly higher than normal levels of substance-based addictions, the difference with the general adult population in relation to this particular addiction within a 12-month period did not differ signifi cantly from large adult samples from Canada, where work and eating were the most prevalent behavioral addictions (Konkolÿ Thege et al, 2015).…”
Section: Prevalence Of Workaholismmentioning
confidence: 59%
“…Across three studies [7, 16, 18*, 25*], individuals with SUDs were consistently rated as substantially more to blame for their condition (59-67%) than individuals with other psychiatric disorders, including schizophrenia (4-6% of respondents endorsing blame).In contrast, only 20% of respondents in the Netherlands study believed that those with addiction had control over it once it started [19]. However, drug addiction was rated as having higher controllability and possibility of recovery with treatment than other psychiatric diagnoses and health conditions (including AIDS and cancer) [23].…”
Section: Resultsmentioning
confidence: 99%
“…Illicit drug addictions were ranked as being more difficult to change without treatment when compared to smoking [24]. A more recently-published study identified addiction liability, or degree of addictiveness attributed to the SUD, as being best able to discriminate among stigmatizing judgements towards SUDs, which may underlie conceptions that SUDs are unlikely to change in the absence of treatment [25*]. …”
Section: Resultsmentioning
confidence: 99%
“…Firstly, both psychiatric conditions could be considered as forming part of the impulse control disorder spectrum, with the most evident shared attribute being the impulsive/compulsive nature of the addictive behavior (Leeman and Potenza, 2012; Grant and Chamberlain, 2014; Di Nicola et al, 2015; Konkolý Thege et al, 2015). Other shared characteristics are the early onset of these problematic/excessive behaviors (Balogh et al, 2013), high exposure to adverse life events (Lee et al, 2012), personality traits characterized by high scores in impulsivity, high levels of emotional-psychological distress (Karim and Chaudhri, 2012), and difficulties in emotion regulation (Williams et al, 2012; Pivarunas and Conner, 2015).…”
Section: Introductionmentioning
confidence: 99%